Does Environmental Uncertainty Affect Entrepreneurs’ Orientation and Performance? Empirical Evidence from Indonesian SMEs - Rina Herani; Otto Andersen (Gadjah Mada International Journal of Business, 2012)
Small and medium enterprises (SMEs) have a critical role in economic growth in Indonesia and become the backbone for job creation, poverty alleviation, and safeguard during the crisis. However, they are highly exposed to uncertain environments. The present study aimed to investigate the influence of SMEs’ entrepreneurial orientation on business performance when uncertain environments exist. A total of 152 Indonesian SMEs were studied in order to assess this relationship. Moderated regression analysis is performed as the main statistical procedures to analyse the moderating role of environmental uncertainty on the influence of entrepreneurial orientation on business performance. Surprisingly, the result of the present study did not confirm the previous predominant studies which found that entrepreneurialorientation dimensions are positively associated with business performance in growing in an uncertain environment. Indonesian entrepreneurs were reluctant to innovate, be proactive, and take risks when an uncertain environment exists. The present study was an endeavour to provide better insight in explaining the inconsistent and ambiguous findings from existing literature.